2019
DOI: 10.1186/s12913-019-4046-9
|View full text |Cite
|
Sign up to set email alerts
|

Understanding healthcare self-referral in Nigeria from the service users’ perspective: a qualitative study of Niger state

Abstract: Background The by-pass of the primary level of care to the referral facilities has continued to raise concerns for the healthcare delivery system. About 60–90% of patients in Nigeria are reported to self-refer to a referral level of care. Thus, this study sought to identify the factors that influence service-users’ decision to self-refer to the secondary healthcare facilities in Nigeria by exploring the perceptions and experiences of the service-users. Methods Twenty-fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
64
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 40 publications
5
64
0
Order By: Relevance
“…The desire of the care seekers to attain quality care from higher tier facilities despite incurring additional transportation cost and longer travel time, is an indication of what they can sacrifice to access quality care. On the other hand, care seekers bypass their nearest sub-county facilities which are mostly faced with inefficient healthcare system [66]. However, the economically challenged population residing far away from the county level facilities may have to contend with the services offered at the local facilities.…”
Section: Discussionmentioning
confidence: 99%
“…The desire of the care seekers to attain quality care from higher tier facilities despite incurring additional transportation cost and longer travel time, is an indication of what they can sacrifice to access quality care. On the other hand, care seekers bypass their nearest sub-county facilities which are mostly faced with inefficient healthcare system [66]. However, the economically challenged population residing far away from the county level facilities may have to contend with the services offered at the local facilities.…”
Section: Discussionmentioning
confidence: 99%
“…10 Several studies have described substantial variation in individual behavior across different health systems, particularly with regard to childbirth facilities. [4][5][6]11,14,17,[20][21][22][23][24][25][26][27][28][29][30][31][32][33] There is limited evidence characterizing the extent of primary health care bypass in Ghana and West Africa in general. A better understanding of these bypass behaviors may provide insights into local primary health care improvement efforts for policy makers and facility managers.…”
Section: Introductionmentioning
confidence: 99%
“…These findings echoed the views of the patients from a previous study, who feared they could be given a wrong diagnosis by the healthcare providers within the PHC facilities. 40 The understanding among the patients that the majority of healthcare providers at the primary level of care were either CHWs or nurses further amplified this concern, thus they voiced their preference to be attended to by doctors who are mainly only available at the higher levels of care. 40 A similar finding was reported in the UK, whereby some patients felt the doctors at the emergency department had better knowledge than their general practitioners, which resulted in seeking care at the referral facility.…”
Section: Discussionmentioning
confidence: 99%
“…40 The understanding among the patients that the majority of healthcare providers at the primary level of care were either CHWs or nurses further amplified this concern, thus they voiced their preference to be attended to by doctors who are mainly only available at the higher levels of care. 40 A similar finding was reported in the UK, whereby some patients felt the doctors at the emergency department had better knowledge than their general practitioners, which resulted in seeking care at the referral facility. 41 Likewise, it's been found that the availability of staff alone does not ensure the delivery of quality care, as healthcare providers can lack the ability to make accurate diagnoses or to appropriately manage patients.…”
Section: Discussionmentioning
confidence: 99%